Pendampingan Penetapan Harga Pokok Produksi Untuk Menentukan Harga Jual Susu Pada KPS-Bogor - Wulansari, Wulansari; Setiawan, Hendra (Jurnal Abdimas Dedikasi Kesatuan, 2024)
This research aims to review the cost of production (HPP) for milk and determine the appropriate selling price in livestock cooperatives. The research was conducted using quantitative descriptive methods and a case study approach on Milk Production Cooperatives and Livestock Businesses. Data collection was carried out through interviews, field observations, and financial report documents for certain periods from the previous year to the month when the final assignment was written. The cost-plus pricing method is used to determine the selling price of pasteurized milk products. Based on this analysis, the results obtained show that the ideal profit margin that can be obtained by each product is between 20-30%. The results of this research can provide an idea of the size of the profit margin on each product so that it can help livestock businesses in calculating HPP accurately and getting maximum profits without harming consumers. Therefore, it is recommended that livestock cooperatives continue to evaluate production costs and determine selling prices in order to increase profits and strengthen competitiveness in the market.   Keywords: Cost of Production, Selling Price, Milk, Cost-Plus Pricing